Narrative Literature Review: Profitabilitas sebagai Determinan Utama dalam Peningkatan Nilai Perusahaan - Nasilem Pangestika; Hijroh Rokhayati (Yayasan Literasi Sains Indonesia, 2025)
Companies, as business entities, are required to sustain strong financial performance in order to enhance firm value while maintaining long-term business continuity. Profitability serves a critical function as an indicator of a firm’s capacity to generate earnings, which subsequently shapes investor perceptions, influences stock prices, and determines market valuation. This study aims to provide a comprehensive examination of profitability as a primary determinant in the creation of firm value. The research employs a narrative literature review approach, synthesizing evidence from eight peer-reviewed articles published between 2015 and 2025 that are directly relevant to the topic. The findings demonstrate that profitability is strongly associated with firm value enhancement, both directly through profit generation and indirectly through improved access to financing, strengthened market reputation, and increased capacity for business expansion. High profitability not only fosters investor confidence but also consolidates a firm’s strategic position within competitive markets. In contrast, low profitability can diminish firm value by eroding investor trust and weakening stock attractiveness. The implications of this review underscore the importance of adopting consistent and measurable profitability management strategies as a central instrument to support the sustainable creation of firm value.